LOCAL POLARIMETRIC SYSTEM FOR MEASURING AIRCRAFT`S NAVIGATION AND PILOTING PARAMETERS - Klochan, A. E.; Al-Ammouri, A.; Subbotyna, V. K.; Palchik, O. P.; Dekhtiar, M. M. (Electronics and Control Systems, 2018)
The paper considers questions of invention the local optical system for measuring navigation and piloting parameters on base on polarimetric technologies. Such system is aimed to increase the sensitivity and accuracy of definition the aircraft navigation and piloting parameters in a locally restricted airspace segment with high traffic density. The paper also deals with regarding existing methods and systems for measuring the aircraft’s piloting and navigation parameters, as well as suggest polarimetric method and the polarimetric system, that realize it. The polarimetric method for measuring the aircraft`s piloting and navigation parameters consist in measuring the polarization plane azimuth of transmitted beam and determining the spatial and plane incident angles of the incident beam, as well as the aircraft`s attitude. Proposed local polarimetric system for measuring aircraft`s navigation and piloting parameters consist two main units: measurement block and radiation block. Radiation block emits the polarized radiation with certain polarization plane azimuth and with certain dispersion aperture. Measurement block measure the polarization plane azimuth of transmitted beam and calculate polarization plane azimuth of incident radiation and its angle of incident. The proposed system allows to measure the piloting, as well as, navigation parameters at the same time with high accuracy and sensitivity. Modeling the operation of the measurement channel shows that dependencies have linear character and match well with measuring parameters. Paper results can be applied in the process of elaboration and implementation of polarimetric navigation system, for example, and requires additional theoretical and practical research.